Biochemical studies on suckling vs nonsuckling buffalo calves in relation to performance of dams - SIKKA, P; SETHI, R K; TOMER, A K S (The Indian Journal of Animal Sciences, 2014)
Effect of weaning on growth has been monitored through biochemical estimations of blood serum proteins, thyroidhormones and immunoglobulins in calves. Alterations in the levels of these biological entities have been considered as the variation due to differences in metabolic status of calves under 2 feeding management at the time of birth. These biochemical changes in serum indicate the metabolic compensation against energy drain due to weaning in the system. However, no differences in body weights were noted in suckling vs nonsuckling calves. The frequency of disease occurrence in nonsuckling calves was higher as compared to suckling calves.